Total synthesis of (3R, 5R) and (3R, 5S)-sonnerlactones. Issue 16 (20th April 2016) - Sanaboina, Chakrapani; Chidara, Sridhar; Jana, Samaresh; Eppakayala, Laxminarayana
Graphical abstract: In this Letter, an enantioselective synthesis of (3 R, 5 R )-sonnerlactone and (3 R, 5 S )-sonnerlactone have been described. Stereochemistry at C-5 position was fixed using a suitable proline catalyzed reaction during the synthesis of aliphatic segment. To accomplish this target, Mitsunobu reaction for inversion of a stereo-centre and ring-closing metathesis (RCM) for macrocyclic ring formations have been applied as key transformations. Highlights: (3 R, 5 R ) and (3 R, 5 S )-sonnerlactone: isolated from the marine derived fungus Zh6-B1. These compounds inhibit the growth of KV/MDR cell line up to certain extent. These lactones exhibit antibacterial, antifungal and anticancer activities. Structural features and important medicinal activity, increased the importance to make these. Mitsunobu reaction and RCM protocol have been applied to construct the core. Abstract: In this Letter, an enantioselective synthesis of (3 R, 5 R )-sonnerlactone and (3 R, 5 S )-sonnerlactone have been described. Stereochemistry at C-5 position was fixed using a suitable proline catalyzed reaction during the synthesis of aliphatic segment. To accomplish this target, Mitsunobu reaction for inversion of a stereocentre and ring-closing metathesis (RCM) for macrocyclic ring formations have been applied as key transformations.